Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trash Như

Thực hiện phép tính:

\(\dfrac{3}{x}-\dfrac{x}{x-1}-\dfrac{x^2}{x+1}-\dfrac{x^2-3}{x^3-x}\)

 

Nguyễn Hoàng Minh
25 tháng 12 2021 lúc 17:24

Nhận thấy \(x^3-x=x\left(x^2-1\right)=x\left(x-1\right)\left(x+1\right)\)

\(\dfrac{3}{x}-\dfrac{x}{x-1}-\dfrac{x^2}{x+1}-\dfrac{x^2-3}{x^3-x}\\ =\dfrac{3x^2-3-x^3-x^2-x^4+x^3-x^2+3}{x\left(x-1\right)\left(x+1\right)}\\ =\dfrac{-x^4+x^2}{x\left(x-1\right)\left(x+1\right)}=\dfrac{-x^2\left(x-1\right)\left(x+1\right)}{x\left(x-1\right)\left(x+1\right)}=-x\)


Các câu hỏi tương tự
Yukino Ayama
Xem chi tiết
Trash Như
Xem chi tiết
ThanhNghiem
Xem chi tiết
Mai Ngọc Hà
Xem chi tiết
Hoang Phương Nguyên
Xem chi tiết
Linh nguyễn
Xem chi tiết
BHQV
Xem chi tiết
Hoàng Huy
Xem chi tiết
Hoàng Huy
Xem chi tiết